COMPARATIVE ANALYSIS OF MUSIC EDUCATION IN UZBEKISTAN AND FINNISH - Omanqulova Sh.N.; Axrorov J.R., (FAN VA TA'LIM INTEGRATSIYASI (INTEGRATION OF SCIENCE AND EDUCATION), 2024)
The article provides general information about the music education system of Finland and Uzbekistan, in which the system, structure, differences and effectiveness of the results of music education in both countries are widely discussed. By adopting the effective aspects of the ehisting methodology in the Finnish music education system, the meaning of educating our young people with awareness of our national values and traditions through our classical music in general education schools is explained in detail.